PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT MADANI SOLUSI INTERNASIONAL JAKARTA SELATAN - Saskia Dyra Adelia; Uswatun Chasanah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. This study aims to examine the impact of Communication and Physical Work Environment on Employee Performance at PT Madani Solusi Internasional, both individually and simultaneously. A quantitative method was applied in this research. The population consisted of 55 respondents, and the sampling technique used was a saturated sampling method, resulting in a total sample of 55 respondents. Data analysis was conducted through validity and reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing.The results showed that Communication (X1) has a positive and significant effect on Employee Performance (Y), as indicated by the regression equation Y = 12.534 + 0.610 X1 and the t-test result where t- count > t-table (5.608 > 2.006), thus H0₁ is rejected and Ha₁ is accepted. Similarly, the Physical Work Environment (X2) has a significant influence on Employee Performance (Y), as shown by the regression equation Y = 12.437 + 0.624 X2 and the t-test result where t- count > t-table (5.224 > 1.670), hence H0₂ is rejected and Ha₂ is accepted.Furthermore, the simultaneous effect of Communication (X1) and Physical Work Environment (X2) on Employee Performance (Y) was also found to be significant. The regression equation obtained is Y = 7.969 + 0.398 X1 + 0.339 X2, with the F-test result showing F-count > F- table (19.448 > 3.18), indicating that H0₃ is rejected and Ha₃ is accepted. This means that both Communication and Physical Work Environment simultaneously have a significant impact on Employee Performance.